A Diagrammatic Analysis of the Supply of Loan Funds - Higgins, Benjamin (Econometrica, 1941)
THE PURPOSE of this paper is to provide a diagrammatic approach to the theory of interest determination, with special emphasis on the supply side of the problem. In Figure 1 the elements which determine the of a particular asset are depicted. On the Y-axis is measured the percentage of of an asset which the individual thinks he can get. Where the asset has no actual value, the term will be used to denote the intrinsic or maximum value which the individual attaches to the assetwhat he thinks it is ultimately worth on the market if he takes to find the most enthusiastic buyer. For the analysis of liquidity as such, we assume that no change in the market value of the asset is expected other than those due to the individual's own action. On the X-axis is the time, measured from the present moment, which the individual thinks it will take to realize the corresponding percentage of face value. The extent to which it pays him to shop around for highbidding buyers depends upon the perfection of his knowledge of the market, which will in turn depend upon the degree of perfection in the market itself. As an individual shops around, his knowledge of the market, and so its perfection, increases. It will be readily seen that assets typically regarded as liquid, such as equities, are assets for which a highly competitive, perfect-knowledge market exists. He is not absolutely certain, however, as to the percentage of face value he can get within a given period, particularly as the begins to get fairly long. Accordingly, we do not have a single cent of face for each point of time, but a probability distribution for each point of time. Probability is measured by the area between two ordinates of the distribution curves, situated in planes parallel to the YZ plane, the total area under each curve being equal to unity. The individual knows exactly what the immediate market value is, so for the x = 0, the height of the probability curve approaches infinity while the width approaches zero. As the shopping period is increased, his estimates become more vague and his degree of certainty diminishes. The dispersion of the probability distribution increases as we move out along the time axis; the curves become lower, flatter, and wider. To each distribution corresponds a single value which can be used to express it: some single value which the individual regards as a situation equivalent to that represented by the distribution, and which could be determined through choice. For example, a certain 75 per cent of face